Financial gatekeepers : can they protect investors? - Fuchita, Yasuyuki, 1958-; Litan, Robert E., 1950- (Nomura Institute of Capital Markets Research ; Brookings Institution Press, 2006)
"Looks at the effectiveness and discusses the appropriateness for further refinement of frameworks designed by policymakers to strengthen investor confidence in corporate financial reporting, especially in the United States and Japan"--Provided by publisher